Comparative evaluation of tomato varieties (Licopersicum esculentum Mill.) in the Forest-Steppe zone of Ukraine - О. Я. Жук; Г. Б. Яременко (Plant Varieties Studying and Protection)
Purpose. Comparative evaluation of varieties of tomato bred by Kyiv experimental station of the Institute of vegetables and melons (IVM) NAAS of Ukraine with allowance for different fruit shapes. Methods. Field, laboratory, statistical ones. Results. Since varietal characteristics can greatly influence the course of the growth process, the experiment included phenological observations of plants growth and development, biometric measurements of plants and fruits, productivity records, besides, biochemical values of fruits with various shape were defined (flat-round and plum-shaped fruits). Varieties with the highest yield, best biochemical values and earlier fruit ripening were identified. Conclusions. Among the samples of tomato with flat-round fruits, Zoren variety had the shortest time interval from mass germination up to early ripening of fruits, Myroliubivskyi variety – in the group of plum-shaped fruits. In the first group Atlasnyi variety had the highest yield, in the second – Khoriv variety. Atlasnyi (flat-round fruits) and Oberig (plum-shaped fruits) varieties had the best biochemical values. Varieties with plum-shaped fruits excelled samples with flat-round fruits at biochemical composition.